NUTRITIONAL STATUS OF RURAL PRIMARY SCHOOL CHILDREN AND THEIR SOCIO-DEMOGRAPHIC CORRELATES: A CROSS-SECTIONAL STUDY FROM VARANASI - Kaushik, Amit; Raj, Richa; Mishra, Chandra Pati; Singh, Sri Prakash (Indian Journal of Community Health, 2012)
Research question: What is the nutritional status of primary school children in rural area of Varanasi and what factors are associated with malnutrition? Objective: To assess the nutritional status of primary school children in rural Varanasi and to find out various socio-demographic correlates of nutritional status. Study Design: Descriptive cross sectional study. Setting: Four primary schools from Chiraigaon Community Development Block of Varanasi were selected for study purpose. Participants: Eight hundred and sixteen students from four schools were involved in the study. Results: Out of total 816 study subjects 429 or 52.6% (201 boys and 228 girls) were underweight and 75 or 9.2% (39 boys and 36 girls) were stunted. Educational status of the parents was found to be significantly associated with the nutritional status of school children Conclusion: As the literacy status of the parents has been revealed to be strongly associated with nutritional status of children, there is an increasing need to focus the efforts towards the parents to improve the nutritional status of primary school children.